A systematic review and content analysis of serious video games for children with ADHD - Schultz, Brandon K.; Evans, Steven W.; Carter, Kaitlynn M.; Dembowski, Allison; Lojinger, Kelly; Murray, Emma R.; Walcott, Christy (Frontiers in Psychiatry, 2025)
Content analysis is a critical step in understanding any mental health treatment, but these details are absent in the serious video games for ADHD literature. To better understand specific ADHD game elements, we conducted a systematic review and identified 37 seminal studies, published between February 2005 and March 2021, investigating 22 distinct ADHD games (final search on January 16, 2025) designed for children and adolescents. We coded those studies and supplementary game descriptions for therapeutic game content, then calculated effect sizes for immediate post-treatment effects on parent ratings of ADHD symptoms (i.e., far transfer), where available. There appeared to be considerable content variability across titles, but most games in this review (55%) attempt cognitive training, with pluralities deploying the go/no-go, continuous performance, and Corsi block tapping task paradigms. Nearly one-fifth (18%) of the games include theta/beta ratio neurofeedback, and more than one-quarter (27%) of the games include novel content (e.g., physical exercise, eye gaze training). Changes in parent ratings of ADHD symptoms range widely (ds = -0.55 to 1.26) without an obvious pattern of advantage for any game element. The largest far transfer effects for ADHD games are found in study results at highest risk of bias, seemingly irrespective of game content. Our findings suggest that far transfer effects are unconvincing for seminal game elements, and that new directions in ADHD game design and delivery are warranted.